71 Identifying Patients with Less Potential to Benefit from Implantable Cardiac Defibrillator Therapy. (6th June 2015) - Kaura, Amit; Mann, Ian; Kamdar, Ravi; Petzer, Edward; Silberbauer, John; Gall, Nicholas; Murgatroyd, Francis; Scott, Paul
Abstract : Background: Implantable cardiac defibrillator (ICD) therapy reduces mortality in selected patients at high risk of sudden cardiac death. However, patients at high risk of non-sudden cardiac death, whose risk of short-term mortality following device implantation is high, may gain no significant benefit from an ICD. A number of approaches have been proposed to identify these high-risk patients, including single clinical markers and more complex scoring systems. The aims of this study were to use the proposed scoring systems to: (1) establish how many current ICD recipients may be too high risk to derive significant benefit from ICD therapy and (2) evaluate how well the proposed scoring systems predict short-term mortality in an unselected cohort of ICD recipients. Methods: We performed asingle-centre retrospective observational study of all new ICD implants over 5years (2009–2013). We used 3 published scoring systems (Kramer et al 1 ; Barsheshet et al 2 ; Parkash et al 3 ) to identify new ICDrecipients whose short-term risk of death following ICD implantation waspredicted to be high. We then evaluated how well the scoring systems predicteddeath during follow-up. Results: Over 5 years there were 406 new implants (79% male, age 67 ± 13 years). The majority (58%) were primary prevention implants and 45% were cardiac resynchronisation therapy-defibrillator devices. During a mean follow-up of 936 ± 560 days, 77 patients died. Using the published scoring systems, the proportion of ICD recipients predicted to be at high risk of short-term mortality were 4% (Kramer), 36% (Barsheshet) and 23% (Parkash). Three-year mortality rates in these high-risk groups were 76%, 32% and 36% respectively; in the overall study population 3-year mortality was 20%. In univariate Cox regression analyses, all 3 scoring systems predicted death (p < 0.001 for each model). However, using multivariate analysis, only the Kramer model remained predictive once serum urea was included in the analysis (p < 0.001). The ROC scores for the prediction of death for the 3 scoring systems and urea were 0.73 (Kramer), 0.69 (Barsheshet), 0.65 (Parkash) and 0.70 (urea). Conclusions: Using published scoring systems, a significant proportion of current ICD recipients are at high risk of short-term mortality following device implantation. Although all 3 scoring systems predicted mortality during follow-up, only the Kramer model added predictive accuracy compared to renal function alone. RENCES: Kramer DB, Friedman PA, Kallinen LM, Morrison TB, Crusan DJ, Hodge DO, Reynolds MR, Hauser RG. Development and validation of a risk score to predict early mortality in recipients of implantable cardioverter-defibrillators. Heart Rhythm 2012;9 :42–6 Barsheshet A, Moss AJ, Huang DT, McNitt S, Zareba W, Goldenberg I. Applicability of a risk score for prediction of the long-term (8-year) benefit of the implantable cardioverter-defibrillator. J Am Coll Cardiol 2012;59 :2075–9 Parkash R, Stevenson WG, Epstein LM, Maisel WH. Predicting early mortality after implantable defibrillator implantation: a clinical risk score for optimal patient selection. Am Heart J 2006;151 :397–403